Saint Nicolas’ Church on the Czwartek Hill in view of current research - Krupa, Karol; Janus, Krzysztof (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2021)
The paper describes known and unknown research works, which took place in the building of Saint Nicolas’ Church on the Czwartek Hill at the M. Słowikowskiego 1 street in Lublin, starting from the 1960s up to the present day. The paper introduce an interdisciplinary way description and presentation of the changes in the structure of the church, phases of transformations and shows the places where older objects could exist before church in current shape.